STRATEGI PEMBELAJARAN PIANO MENGGUNAKAN NOTASI ANGKA DI ELFA'S MUSIC SCHOOL CIMAHI - Putri, Faradhia Khanza (2016)
The assumption numeral notation is easier than beam notation in Indonesia make a notation of the numbers are still widely used, especially in formal schools. Elfa's Music School in Cimahi, numeral notation is still used for the piano lessons. This study was conducted because researchers wanted to know how the notation numbers that have limited tone areas can be used for learning piano tone that has wide area and many tones that can be played at one time. Issues examined include the initial step introduction numeral notation and learning piano technique using notation numbers. This descriptive study used a qualitative approach. Data collection techniques used in the study is observation, interview and documentation. The results showed that there are two ways of learning, the first steps starting from the identity of the tones on the piano, the symbol numbers, pronunciation Solmization. The second began with the sign of the number, the identity of the tone on the piano, the pronunciation Solmization. Learning piano notation numbers makes it difficult to play a different tonal. Based on this result,teachers suggestedto do an introduction for beam notation to their students.